A quantitative investigation into women's basic beliefs about birth and planned birth choices. (August 2018) - Preis, Heidi; Gozlan, Miri; Dan, Uzi; Benyamini, Yael
Highlights: Basic beliefs about birth as a natural or a medical process are distinct concepts. They are both pivotal in explaining women's birth-related choices. The medical and natural beliefs interact in their association with birth choices. Endorsing natural while rejecting medical beliefs relates to more natural choices. Fear of birth is not associated with birth choices in the presence of the beliefs. Abstract: Objective: Perceptions about the nature of the birth process are important in determining women's birth choices regarding labour and delivery but are scarcely the subject of empirical research. The aim of the current study was to assess women's beliefs about birth as a natural and safe or medical and risky process and study the associations of these beliefs with fear of childbirth and planned birth choices. Design: An observational study using self-administered questionnaires during pregnancy. Setting: 1. Community women's health centres in a metropolitan area in Israel; 2. Purposeful sampling of women who plan to birth naturally, through home midwives and targeted internet forums. Participants: 746 women with a singleton pregnancy in their second and third trimester. Measurements: Beliefs about birth as a natural and a medical process, fear of childbirth, and a range of natural birth choices. Findings: The birth beliefs were associated with women's birth intentions. The more women believed birth to be natural and the less they believed it to be medical, the more likely they were to make more natural birth-related choices. In the presence of the birth beliefs, fear of childbirth no longer had an independent association with birth choices. The beliefs interacted with each other, revealing a stronger association of viewing birth as natural with planning more natural choices among women who did not view birth as very medical. Key conclusion: It is important to recognize women's beliefs about birth and how they may affect their fear of childbirth and birth intentions. Further studies on the origin of such beliefs and their development are needed. Implications for practice: Women should be allowed to choose how they would like to birth in accordance with their beliefs. At the same time, strengthening women's belief in the natural birth process and their body's ability to perform it, could help lower fear of childbirth and medical intervention rates.